THE ROLE OF TOURISM IN CREATING MENTAL HEALTH AMONG GEN Z IN BATU - Andini Sakti, Aileen; Satrya, I Dewa Gde (Universitas Nahdlatul Ulama Surabaya, 2025)
This study examines the role of tourism in improving mental health, with a focus on its impact on Generation Z in Batu. The COVID-19 pandemic, which has affected the world since early 2020, led to an increase in mental health issues across various groups, particularly among the younger generation. One of the responses to this situation was the growing awareness of the importance of